Efektivitas Pendidikan Kesehatan Menggunakan Media Buku Kesehatan Jiwa Berbahasa Lokal Terhadap Pengetahuan Kesehatan Jiwa Remaja SMA di Kabupaten Kupang - Riantiarno, Flavianus; Suhardin, Saverinus; Lagut, Yosefina Frisnarati Novita; Dee, Theodehild M. Theresia; Sakinah, Siti; Lote, Rian Rifaldo; Bire, Deriensi D. Aprilin (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Mental health problems in adolescents are a serious health problem. There is an increase in mental health problems in adolescents. Knowledge is one of the contributing factors. Mental health knowledge can make the right decisions about their own mental well-being and seek help when they need it. Health education is an effort to increase knowledge. Many studies use health media to increase mental health knowledge. The novelty in this study is the use of local language health pocket books. The purpose of the study was to determine the effectiveness of health education using local language mental health pocket books on adolescent knowledge of mental health. This type of research is a Quasi Experiment with a Pretest and Posttest two Group Design research design. The sample size was 150 respondents, with a sampling technique: purposive sampling. Data collection using a knowledge questionnaire in the pre-test and post-test. The results of the study using the Wilcoxon test showed that health education using local language books was effective in increasing adolescent mental health knowledge with a p value of 0.000 (p <0.05). In conclusion, local language Mental Health Books can be used to improve adolescent mental health knowledge.